2020
DOI: 10.1111/nhs.12781
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Suicide Second Victim Experience and Support Tool: Psychometric properties of a scale for nurses who experienced inpatient suicide at Chinese general hospitals

Abstract: This study describes a psychometric scale, the Inpatient Suicide Second Victim Experience and Support Tool, for evaluating physical and psychological distress with a focus on resources for supporting the needs of nursing professionals. Our study defines "second victim" as a nurse who experiences inpatient suicide while on shift. We conducted a cross-sectional study among non-psychiatric nurses to examine the psychometrics of the scale. A total of 731 participants were recruited from eight Chinese general hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Tan et al added emphasis on health practitioners being second victims of inpatient suicide. 3 While the clinical practice of nurses was negatively affected by inpatient suicide, it also had a formative influence. This study confirms Matandela et al who also found that inpatient suicide resulted in a diminished sense of professional competency, including feelings of guilt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al added emphasis on health practitioners being second victims of inpatient suicide. 3 While the clinical practice of nurses was negatively affected by inpatient suicide, it also had a formative influence. This study confirms Matandela et al who also found that inpatient suicide resulted in a diminished sense of professional competency, including feelings of guilt.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In the classification of adverse nursing events in a hospital, Chinese inpatient suicide is categorised as accidental and unpredictable. 3 Suicide fatalities in hospital wards can cause severe trauma to both patients and staff members. Consequently, both groups may develop maladaptation with poor coping skills.…”
Section: Introductionmentioning
confidence: 99%
“…In was not conducted to find latent variables (Ajoudani et al, 2021). In Tan et al's study,21 items in four factors were extracted using the maximum-likelihood and Promax rotation methods (Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the study of these researchers were nurses working in general wards, also, EFA was not conducted to find latent variables (Ajoudani et al, 2021 ). In Tan et al's study, 21 items in four factors were extracted using the maximum‐likelihood and Promax rotation methods (Tan et al, 2020 ). In the study of Strametz et al ( 2021 ), 11 factors were extracted using the principal component analysis.…”
Section: Discussionmentioning
confidence: 99%